Impact evaluation combining ability of tomato hybrids and lines for production and fruit quality traits - Essa, Bassim Almass (2024)
Introduction. The selection of pure lines followed by crosses to create superior hybrids is one of the oldest strategies in crop breeding. Combining ability studies provide reliable information for selection of parents for hybrid combination by revealing the nature and magnitude of gene actions involved in expression of quantitative traits. Objective. To estimate the general and specific combining ability (GCA and SCA) values for yield in cherry tomatoes and select F1 hybrids combining high yield and fruit quality traits. Materials and methods. The half-diallel design, following method 2 of Griffing was used to define the best breeding method. Five lines were crossed to produce ten hybrid combinations using a half diallel design involving the parents. Crosses and evaluations were conducted in a greenhouse in the Experimental Station at the University of Diyala, Baqubah, Iraq, in the winter of 2022-2023. Results. Based on GCA effects, lines LA353, LA3899 and IQ2 could be potential donor parents in breeding. Based on average performance, heterosis manifested and SCA effects, crosses IQ2×LA4013, LA3899×LA353 and IQ2×LA3899 were best in respect to yield and fruit quality. Conclusion. The general and specific combining ability values for most of the traits supported the material’s great variety. The magnitude of heterosis was improved compared to parental lines. The high-yielding parent lines LA3899 and IQ2 could be used for breeding cherry tomatoes under greenhouse conditions.